Racial equality in America - Franklin, John Hope, 1915-2009. (Columbia : University of Missouri Press, 1993)
Traces the history of America's racial inequality, discussing the disparity between the goal of racial equality and the facts of discrimination.
Originally published: Chicago : University of Chicago Press, 1976. (Jefferson lecture in the humanities; 1976).
Includes bibliographical references (pages 109-113) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: African Americans -- History; African Americans -- Civil rights; Noirs américains -- Histoire; Noirs américains -- Droits; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; African Americans; African Americans -- Civil rights; Rassenongelijkheid; Verenigde Staten; History